Chapel at the Club of St. Anthony - Mumbai Archive Project (Jio Institute, 2024)
The chapel at the Club of St. Anthony is typical of those found in Goan homes, where a chapel is designated for use by family members. The chapel offers a shared space for prayer, reflection, and gathering during festivals. Spaces like these emphasize the importance of Goan identity, religious traditions, and the sense of community that defines the unique character of the clubs.